2005
DOI: 10.1093/ps/84.4.667
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to antibiotics: chemical and physical antimicrobial interventions and foodborne pathogen response

Abstract: Successful control of foodborne pathogens requires placement of chemical and physical hurdles in the preharvest and postharvest food production sectors. Pathogens may also encounter indigenous antimicrobials in foods including certain botanical compounds that have historically been used for flavor enhancement as well as preservation. Chemical additives have traditionally included organic acids to control microbial contamination in foods and feeds. However, there is some concern that continuous application of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 96 publications
0
49
0
2
Order By: Relevance
“…The increasing effect of antibiotics on ADFI is mostly due to the depression of microbial populations of intestine especially the harmful ileal and cecal microbiota. These microbial colonies could produce toxic compounds and gases that damage epithelial cells and reduce bird's appetite (Ricke et al, 2005;Tellez et al, 2006). In this regard, it has been demonstrated that the harmful intestinal microbial colonies were diminished by administration of different flavonoid and isoflavonoid compounds (Bankova et al, 2000;Havsteen, 2002;Kosalec et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The increasing effect of antibiotics on ADFI is mostly due to the depression of microbial populations of intestine especially the harmful ileal and cecal microbiota. These microbial colonies could produce toxic compounds and gases that damage epithelial cells and reduce bird's appetite (Ricke et al, 2005;Tellez et al, 2006). In this regard, it has been demonstrated that the harmful intestinal microbial colonies were diminished by administration of different flavonoid and isoflavonoid compounds (Bankova et al, 2000;Havsteen, 2002;Kosalec et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of ASC is the ability to maintain antimicrobial efficacy even in the presence of extraneous organic matter (Cherrington et al 1992) unlike chlorine (Ricke et al 2005). Combination of thermal treatment and antimicrobial treatments are, therefore, needed that are practical, cost-effective and safe to use while maintaining the organoleptic attributes of poultry meat.…”
Section: Introductionmentioning
confidence: 99%
“…Removal of these antimicrobials will induce changes within the chicken intestinal microbial flora, dictating the need to further understand the microbial ecology of this system (Knarreborg et al, 2002;Wise and Siragusa, 2007), so that appropriate antibiotic alternatives may be developed based on this knowledge (Cotter et al, 2005;Ricke et al, 2005). There has been a limited number of new antibiotic drugs marketed recently with only two, linezolid which targets bacterial protein synthesis and daptomycin wherein the mechanism of action is unknown, appearing since 2000.…”
Section: Antibiotics Antibiotic Resistance and The Future Role Of Bamentioning
confidence: 99%